Between tradition and evidence in Orofacial Harmonization: Post-application care of Botulinum Toxin (Research, Society and Development, 2025)
Objective: To critically analyze the recommendations and post-application care for botulinum toxin type A, differentiating scientifically based guidelines from empirical practices still present in clinical practice, in order to promote safer, more effective, and evidence-based management. Methodology: A literature review was conducted to gather and evaluate scientific publications related to post-application guidelines for botulinum toxin type A. The search was conducted in PubMed, SciELO, Medline, and LILACS, using the descriptors "Botulinum Toxin A," "Myths," "Guidance," and "Postoperative Care." Articles in Portuguese, English, and Spanish that addressed recommendations after the use of the toxin were included. Duplicates and texts without full access were excluded. Results and Discussion: The analysis revealed that several widely disseminated recommendations, such as avoiding lying down for four hours, not exercising, or not touching the treated area, lack consistent scientific support. Many of them derive from empirical practices perpetuated without proof. Conversely, guidelines such as avoiding excessive manipulation of the area and informing the patient about possible adverse effects are partially supported. It was observed that excessive unfounded recommendations can generate insecurity and compromise the professional-patient relationship, highlighting the importance of evidence-based guidelines. Conclusion: It is concluded that most post-botulinum toxin recommendations lack scientific proof. Therefore, it is essential to adopt evidence-based practices, dispel myths, and strengthen communication with patients, aiming for a more rational, safe, and individualized clinical practice.